Kinerja Keuangan Perusahaan Komunikasi yang Terdaftar di Bursa Efek Indonesia Selama Pandemi Covid-19 Tahun 2019-2020 - Hariany Idris (Jurnal Mirai Management, 2021)
PT. Bakrie Telecom Tbk is a telecommunication communication operator company based on Code Division Multiple Access (CDMA) in Indonesia, previously known as PT. Radio Telephone Indonesia (Ratelindo). The company was founded in August 1993 as a subsidiary of PT. Bakrie and Brothers Tbk. The purpose of this journal is to analyze the financial statements of PT. Bakrie Telecom Tbk, during the period 2019 to 2020. The data information used to analyze these financial statements is obtained from the Indonesia Stock Exchange (IDX) in a transparent manner. The method used to measure the company's financial performance is descriptive research method. Keywords: PT. Bakrie Telecom Tbk, Financial Statements, Financial Statement Analysis